Mengetahui Tingkat Pengetahuan dan kesadaran Generasi Z dalam Menerapkan Diet Rendah Karbohidrat - Nazmi Izdihar Nur Aliyah; Nisrina Qurrotul’aini; Widhi Nurrohman; Yosephin Berliana Terra Rosa (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Low-carb diets are one of the strategies for weight loss for people with obesity, diabetes, or some other diseases that require dieting in order to reduce the consumption of carbohydrates in food. Gen Z is accustomed to the digital world and easy access to information, some of them have a good understanding of carbohydrate diets and their effects on health. This journal aims to determine the level of knowledge, awareness, and how many have implemented a low-carb diet among generation Z. From 60 respondents who filled out the questionnaire, it was found that 78.3% of Generation Z already knew what a low-carb diet was, and 66.7% of Generation Z were interested in trying a low-carb diet.